Rare missense coding variants in oxytocin receptor (OXTR) in schizophrenia cases are associated with early trauma exposure, cognition and emotional processing. (February 2018) - Veras, Andre B.; Getz, Mara; Froemke, Robert C.; Nardi, Antonio Egidio; Alves, Gilberto Sousa; Walsh-Messinger, Julie; Chao, Moses V.; Kranz, Thorsten M.; Malaspina, Dolores
Abstract: Background: Oxytocin is a peptide hormone that influences the integration of social cognition with behavior and affect regulation. Oxytocin also prominently directs the transition of neuronal GABA neurotransmission from excitatory to inhibitory after birth. The oxytocin receptor ( OXTR ) is linked to schizophrenia, a heterogeneous syndrome. Relationships of OXTR polymorphisms with specific clinical features could aid in evaluating any role of oxytocin in the pathogenesis of schizophrenia. Method: Schizophrenia cases with rare missense coding OXTR single nucleotide variants (SNVs) were identified from a well-characterized sample of cases and controls who were assessed for symptoms, cognition and early life trauma. Results: Five of 48 cases showed rare OXTR variants. Compared to the other cases they had less severe negative symptoms (deficits in emotional expression and motivation) and less severe general psychopathology scores (depression and anxiety). They demonstrated lower nonverbal (performance) than verbal intelligence due to deficient perceptual organization and slow processing speed. They also reported greater early trauma exposure (physical and sexual abuse and emotional trauma). Conclusion: Cases carrying rare OXTR SNVs had less negative and affective symptoms than other cases, but similar psychotic symptoms, along with specific cognitive deficits. The clinical characterization of these cases occurred in association with environmental exposure to early trauma, especially sexual abuse, which may have influenced the expression of schizophrenia in subjects harboring specific SNVs in the OXTR .